USING ETHNOMATHEMATICS FROM BATIK JEMBER TO CREATE ELECTRONIC MODULES - Milenia, Bella Bunda; Suryaningrum, Christine Wulandari; Rhomdani, Rohmad Wahid (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2022)
The purpose of this study was to determine the process and results of developing an ethnomathematics-based e-module on Jember batik motifs for high school students. The type of research used is Research and Development (R&D) with the research model used is the ADDIE research and development model (Analyze, Design, Development, Implementation, Evaluation). Data collection instruments in the form of validation sheets, student response questionnaire sheets and question sheets. The trial subjects in this study were limited to 6 students in class XI IPA at SMA Negeri Pakusari, while for the large scale trial, the remaining limited scale trials were from students in class XI IPA at SMA Negeri Pakusari. The data analysis techniques used are product validity analysis, practicality analysis, and effectiveness analysis. Based on the results of the analysis, it is found that the ethnomathematics-based e-module on Jember batik motifs for high school students has met three categories of product quality assessment, namely validity, effectiveness, and practicality and can be declared successful or feasible to use. Thus, the product can be useful as a learning resource and to facilitate students in learning mathematics and culture